Human dendritic cells efficiently phagocytose adenoviral oncolysate but require additional stimulation to mature - Schierer, Stephan Reinhard; Nettelbeck, Dirk M. (International journal of cancer, 2011)
Oncolytic adenoviruses are emerging agents for treatment of cancer by tumor-restricted virus infection and cell lysis. Clinical trials have shown that oncolytic adenoviruses are well tolerated in patients but also that their antitumor activity needs improvement. A promising strategy toward this end is to trigger systemic and prolonged antitumor immunity by adenoviral oncolysis. Antitumor immune activation depends in large part on antigen presentation and T cell activation by dendritic cells (DCs). Thus, it is likely that the interaction of lysed tumor cells with DCs is a key determinant of such “oncolytic vaccination.” Our study reveals that human DCs effectively phagocytose melanoma cells at late stages of oncolytic adenovirus infection, when the cells die showing preferentially features of necrotic cell death. Maturation, migration toward CCL19 and T cell stimulatory capacity of DCs, crucial steps for immune induction, were, however, not induced by phagocytosis of oncolysate, but could be triggered by a cytokine maturation cocktail. Therefore, oncolytic adenoviruses and adenoviral oncolysate did not block DC maturation, which is in contrast to reports for other oncolytic viruses. These results represent a rationale for inserting immunostimulatory genes into oncolytic adenovirus genomes to assure critical DC maturation. Indeed, we report here that adenoviral transduction of melanoma cells with CD40L during oncolysis triggers the maturation of human DCs with T cell stimulatory capacity similar to DCs matured by cytokines. We conclude that triggering and shaping DC-induced antitumor immunity by oncolytic adenoviruses “armed” with immunostimulatory genes holds promise for improving the therapeutic outcome of viral oncolysis in patients.